Dynamic Characteristics for Leveling System of Mobile Elevating Work Platforms - Xue-peng Cao; Sheng-jie Jiao; Lei Cheng; Jun Zhang; Jin-ping Li (Institute of Advanced Engineering and Science, 2014)
Focused on revealing variations of dynamic characteristics of an auto-leveling system used in mobile elevating work platforms (MEWP) at large height, a unified mathematical model composited of a series of sub-models was built for the leveling systems. An effect on dynamic characteristics including the fast response and relative stability from varying-parameters was investigated. Results displayed the displacement-angle factor changing with work-conditions tended to cause fluctuations of the stability, while enlarging the amplifier gain would accelerate system response. Increasing the area ratio was conducive to leveling stability to be reinforced, but lead a different response speed for forward process or reverse leveling, which was harmful to overall stability. The findings would provide essential theory guidance for the design and manufacture of the leveling system devices of high altitude platform. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4914